THE APPLICATION OF GROUP COUNSELING USING ANIMATED FILMS TO MOTIVATE THE RECOVERY OF CHILDREN WITH CANCER AT THE SEHAT CERIA SHELTER FOUNDATION - Wiwit Pratiwi; Suryati Suryati; Emi Puspita Dewi (LP2M IAI Al-Khairat Pamekasan, 2025)
Children with cancer not only face physical challenges due to their illness and lengthy treatment process, but also experience psychological stress that can reduce their motivation to recover. This condition requires psychosocial support services that can support children's emotional well-being and improve their zest for life. This study aims to describe the application of group counseling using animated films and analyze its contribution to motivating the recovery of children with cancer at the Rumah Singgah Sehat Ceria Foundation. This study uses a qualitative approach with a descriptive design. The research subjects consisted of children with cancer who participated in group counseling services, foundation assistants, and counselors. Data collection techniques included participatory observation, in-depth interviews, and documentation. The data were analyzed using an interactive analysis model through the stages of data reduction, data presentation, and conclusion drawing, and their validity was tested through source and technique triangulation. The results showed that the application of animation-based group counseling was able to increase children's involvement in group activities, encourage emotional openness, and strengthen social interaction and support among group members. Animation effectively served as a stimulus that helped children express their feelings and internalize positive values such as hope, courage, and optimism. In addition, there was an increase in healing motivation, as demonstrated by a more optimistic attitude, acceptance of the disease, and a greater willingness to undergo treatment. Based on these findings, it can be concluded that group counseling using animated films is an effective and relevant approach to increase healing motivation and the psychological well-being of children with cancer. This approach is recommended for development in psychosocial services at shelters and institutions that support children with cancer.